2016
DOI: 10.1002/jcb.25592
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Mutations in Head and Neck Squamous Cell Carcinoma and Their Impact on Disease Progression and Treatment Response

Abstract: Recent studies describing the mutational landscape of head and neck squamous cell carcinoma (HNSCC) on a genomic scale by our group and others, including The Cancer Genome Atlas, have provided unprecedented perspective for understanding the molecular pathogenesis of HNSCC progression and response to treatment. These studies confirmed that mutations of the TP53 tumor suppressor gene were the most frequent of all somatic genomic alterations in HNSCC, alluding to the importance of the TP53 gene in suppressing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
266
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(297 citation statements)
references
References 50 publications
25
266
2
4
Order By: Relevance
“…By this indicator, only one of the HPV-positive tumors (UP1880, p16 score= 1) among the HIV-infected cases was not driven by the HPV16 viral DNA found in the tumor. Among the HPV-positive tumors from HIV-negative controls, one (UM2495) failed to express p16, and two others (UM1349 and UM 1803) expressed only low levels of p16, raising a question about whether the virus is a driver in these cases or if p16 has been completely or partially inactivated by other mechanisms such as methylation or copy loss (1922). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By this indicator, only one of the HPV-positive tumors (UP1880, p16 score= 1) among the HIV-infected cases was not driven by the HPV16 viral DNA found in the tumor. Among the HPV-positive tumors from HIV-negative controls, one (UM2495) failed to express p16, and two others (UM1349 and UM 1803) expressed only low levels of p16, raising a question about whether the virus is a driver in these cases or if p16 has been completely or partially inactivated by other mechanisms such as methylation or copy loss (1922). …”
Section: Discussionmentioning
confidence: 99%
“…Generally when TP53 is wild type, little or no TP53 protein expression is seen in the tumor; however, TP53 protein expression is often high in tumors with mutant TP53 (22). Among the HPV-positive tumors from HIV-positive cases, TP53 expression was low or moderate in all but one tumor (UM2359, p53 score= 12)).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that mutations in the p53 gene and decreased p53 expression contributed to cancer progression . The expression of TSPAN2 and TSPAN12 was increased following the down‐regulation of p53.…”
Section: Discussionmentioning
confidence: 95%
“…While tumor HPV status remains one of the strongest biomarkers for predicting outcome of SCCOP, identification of novel and robust biomarkers for predicting HPV status in SCCOP is clinically useful. As HPV(+) SCCOP patients have heterogeneous clinical outcomes, 25 it is possible for physicians to optimize patient actually inactive or less active. 55,56 In another study, HPV16 E6 mediated degradation was dominant over MDM2 in cervical cancer.…”
Section: Mdm4 Rs4245739 Genotypes Are Associated With Survival Of Smentioning
confidence: 99%
“…[19][20][21][22][23] Thus, identifying molecular biomarkers which may lead to improved survival for patients with SCCOP is urgently needed. p53 as an important tumor suppressor plays a critical role in genome integrity and acts as "the guardian of genome" in many human cancers, especially in squamous cell carcinomas of the head and neck (SCCHN), 24,25 while mouse double minute 2 (MDM2) and 4 (MDM4) inhibit the tumor suppressor activity of p53 through the interaction between p53 and the two negative modulators. [26][27][28] MDM4 is an oncoprotein which negatively regulates the p53.…”
Section: Introductionmentioning
confidence: 99%